The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.15640/smq.v3n1a3
|View full text |Cite
|
Sign up to set email alerts
|

Impact Analysis of Tax Policy and the Performance of Small and Medium Scale Enterprises in Nigerian Economy

Abstract: The mortality rate of Small and medium enterprises which make up 95% of the economy is very high and these Small and medium enterprises serve as source of employment generation; innovation, competition, and economic dynamism in the development of Nigerian Economy. Tax policy is one of the factors that constitute the Small businesses' economic environment. Therefore, the objective of this study impact analysis of tax policy and the performance of small and medium scale enterprises in Nigerian economy is to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 1 publication
(1 reference statement)
0
12
0
Order By: Relevance
“…The current paper aims to empirically examine the impact of SMEs sector on FDI inflows and the role of IFRS adoption in Algeria. Based on previous literature (Esther et al, 2018;Eze and Okpala, 2015), the basic regression equation of this empirical study can be specified as:…”
Section: Model Specification and Estimation Techniquementioning
confidence: 99%
“…The current paper aims to empirically examine the impact of SMEs sector on FDI inflows and the role of IFRS adoption in Algeria. Based on previous literature (Esther et al, 2018;Eze and Okpala, 2015), the basic regression equation of this empirical study can be specified as:…”
Section: Model Specification and Estimation Techniquementioning
confidence: 99%
“…International Journal of Accounting and Taxation, Vol. 6(2), December 2018 Bateman (2013) asserted that 90% of owners of business identified that taxes were a serious barrier to their businesses (Ocheni, 2015). Multiple taxations are common in Nigeria (Adebisi & Gbegi, 2013).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…According to Ocheni, (2015); The principle of ability to pay theory of taxation started in the 16 th Century. It was further extended by the Swiss philosopher Jean Jacques Rousseau (1712-1778), and the French political economist Jean Baptiste Say (1767-1832).…”
Section: Ability To Pay Theory Of Taxationmentioning
confidence: 99%
See 2 more Smart Citations